Tinjauan Yuridis Dalam Sistem Perbankan Digital Terhadap Perlindungan Nasabah - Vehrial Vahzrianur; Samudra Farasi Putra; Rizky Bayu Pratama; Muhamad Revanza Solihin; Aditya Pangestu Halomoan Tampubolon; Farahdinny Siswajanthy (Deposisi: Jurnal Publikasi Ilmu Hukum, 2023)
Juridical Review of the Digital Banking System for Customer Protection discusses legal certainty for customers in banking transactions via internet banking. The study highlights the protection of customers' personal data and the security of banking information regulated in related agreements including Law no. 10 of 1998 concerning banks and Law no. 11 of 2008, which was changed to Law no. 19 of 2016 concerning electronic information and transactions. Legal protection of online banking users from cybercrime also serves as a research focus. Several studies also highlight the importance of policy protection for victims of economic crime in the banking sector. Customer protection in digital banking systems is becoming increasingly important along with rapid technological developments